Chronic thinner intoxication: clinico-pathologic report of a human case. Issue 11 (November 1980) - Escobar, A; Aruffo, C
Abstract : A 27 year old Mexican male addicted for 12 years to glue-sniffing and thinner inhalation developed neurological and behavioural disturbances which led to hospital admission and death. Autopsy disclosed diffuse cerebral and cerebellar cortex atrophy and giant axonopathy both central and peripheral. The corpus callosum was atrophic secondarily to neuron loss in the neocortex.